The role of criticism in understanding problem solving : Honoring the work of John C. Belland - Belland, Brian R.; Fee, Samuel B. (Explorations in the Learning Sciences, Instructional Systems and Performance Technologies, 2012)
The concept of criticism as a tool for research, although well established in other educational research traditions,  is not well established in the domain of Educational Technology. This book changes all that by substantiating criticism as a way to step back and critically evaluate an educational intervention within educational technology. Doing so provides an valuable approach for researchers in terms of  guiding meta analyses and theoretical studies, preventing the proverbial "spinning of the wheels" that often happens in educational research. The book looks back to the seminal work in the field, Paradigms regained: the uses of illuminative, semiotic, and post-modern criticism as modes of inquiry in educational technology - a book of readings by Denis Hylinka and John Belland, as a guidepost and then extends and updates the ideas found within it. But the authors do much more then merely take that work forward. They re-evaluate it, consider the state of the field today, and propose ways in which educational researchers might think of heading forward in their studies of the theory that drives practices in educational technology and instructional design. The authors revisit the ideals of criticism, establishing their usefulness for studying Educational Technology interventions supporting problem based learning. Through the use of focused, specific case studies, the book provides a multitide of new research questions and directions and proves criticism can profoundly invigorate the field of educational research.  This book was written to provide not only a reconsideration of pre-existing knowledge, but as an originator of new ideas. It represents a complete overhaul and rethinking of the use of criticism as a method for understanding and furthering the research area of PBL within the field of Educational Technology and Instructional Design ; it will prove, however, to be an important resource for researchers working in any area of Educational Technology who are hungry for a new approach to research.